Cooperative identity: a systematic literature review - Júlia Elisabete Barden; Deivid Ilecki Forgiarini; Fernanda Cristina Wiebusch Sindelar; Carlos Cândido da Silva Cyrne; Alexandre de Souza Garcia (Boletín de la Asociación Internacional de Derecho Cooperativo)
Cooperatives driven by the Cooperative Identity have a scope of action that goes beyond their economic purposes. This article aims to understand how the Cooperative Identity has been discussed between the years 2019 to 2023. A systematic literature review was conducted using the Methodi Ordinatio approach on databases, and the content was analyzed using Mendeley®, VOSviewer®, and NVivo® software. The results indicate a prevalence of discussions on the 5th principle (Education, Training, and Information) and little discussion on the other six principles. Among the principles not discussed are those that impact management and, in turn, can strengthen the Cooperative Identity. In general, cooperatives are mainly treated as mere subjects of study.